2014
DOI: 10.3389/fcimb.2014.00007
|View full text |Cite
|
Sign up to set email alerts
|

Virulence profiling of Shiga toxin-producing Escherichia coli recovered from domestic farm animals in Northwestern Mexico

Abstract: Shiga toxin-producing Escherichia coli (STEC) is a zoonotic enteric pathogen that causes human gastrointestinal illnesses. The present study characterized the virulence profiles of O157 and non-O157 STEC strains, recovered from domestic animals in small rural farms within the agricultural Culiacan Valley in Mexico. Virulence genes coding for adhesins, cytotoxins, proteases, subtypes of Shiga toxin (Stx), and other effectors were identified in the STEC strains by PCR. The genotyping analysis revealed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 85 publications
4
26
0
Order By: Relevance
“…A total of 59 STEC O157:H7 and non-O157 strains were isolated from domestic animal feces in small rural farms, near agricultural fields in the Culiacan Valley, Northwestern Mexico [ 16 , 22 ]. The source, serotype and virulence potential of the tested STEC strains were previously characterized [ 16 , 22 ]. STEC strains were routinely grown at 37 °C on trypticase soy agar (Bioxon, Mexico City, Mexico) under aerobic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 59 STEC O157:H7 and non-O157 strains were isolated from domestic animal feces in small rural farms, near agricultural fields in the Culiacan Valley, Northwestern Mexico [ 16 , 22 ]. The source, serotype and virulence potential of the tested STEC strains were previously characterized [ 16 , 22 ]. STEC strains were routinely grown at 37 °C on trypticase soy agar (Bioxon, Mexico City, Mexico) under aerobic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Argentina, where the HUS is endemic, hold the highest record worldwide of this syndrome with an incidence of 17/100,000 children less than 5 years old ( Rivas et al, 2010 ). Although STEC O157:H7 is recognized as the most important serotype associated with human infection, there are more than 400 non-O157 serotypes that have been involved in human disease and isolated from different reservoirs including cattle, pigs, goats, sheep, cats, and dogs ( Parma et al, 2000 ; Padola et al, 2004 ; Amézquita-López et al, 2014 ). STEC usually do not produce disease in animals, however, the Stx2e subtype is involved in edema disease in pigs, a peracute toxemia characterized by vascular necrosis, edema, neurological signs and that in some cases can be fatal ( Niewerth et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Small Ruminant Research 153 (2017) 41-47 Another diarrhea causing STEC serotype in human population is O146:H21, in this investigation four isolates are reported with expression of stx 1 and stx 2 genes. Researches in other countries reported this same serotype from healthy adult sheep and lambs, in Spain Rey et al, 2003;Mora et al, 2005); Mexico (Cuenca-Verde et al, 2013Amézquita-López et al, 2014, Brazil (Vettorato et al, 2009) and Norway (Urdahl et al, 2001) isolates from healthy adult sheep and lambs. Serotypes O104:H7 and O146:H21 along with O76:H19 serotype (with expression of stx 1 gene) and ONT:H21 (with expression of stx 1 gene) found in this study are responsible for cases of diarrhea in humans in Mexico; which makes these serotypes, in particular, a possible risk factor for public health (Eslava et al, 1994).…”
Section: Discussionmentioning
confidence: 81%
“…In Mexico, few studies have been conducted to determine the presence of STEC strains and their virulence factors in cattle carcass, sheep and feces of domestic animals. Amézquita-López et al (2014) found 12.5% prevalence of STEC, 5.4% of isolates were O157 and 7.1% of isolates were No-O157, in feces of healthy domestic animals (cattle, sheep, pigs and poultry) of small rural farms in the valley of Culiacan northwestern Mexico. Cuenca-Verde et al (2013) found 26% prevalence of STEC No-O157 in feces of healthy sheep in one technified farm in Jalisco, Mexico.…”
Section: Introductionmentioning
confidence: 89%